“Costos de producción para la elaboración de camas y control de precios en la ebanistería “Picapiedra” del cantón La Maná 2020”. - Cortez Sandoval, Karina Jasmin (2021)
The present investigation entitled, "Production costs for the manufacture of beds and price control in the cabinetmaker" Flintstone "of the canton La Maná 2020" The investigation was raised based on the problems faced by the cabinetmaker that is associated with ignorance of the elements of the cost, this does not allow the real costs related to raw material, labor and indirect manufacturing costs to be identified, so it results in a higher expense than expected since the activities for production are based In empirical records, this is where the problem arises: How does the profitability of the microcredit operations of the Savings and Credit Cooperatives affect the socio-economic development of the La Maná canton? With this, the main objective is proposed, which is to analyze the production costs required in the elaboration of beds for their adequate price control in the “Flintstones” cabinetmaker of the La Maná canton. Based on the research, the proposal called MANUAL PROPOSAL OF COSTS BY PROCESSES FOR THE “PICA PIEDRA” EBANISTERY is made, based on a manual of costs by processes with relevant information that serves as a guide for the determination, calculation and apportionment of the costs of providing Relevant information regarding the process cost methodology that serves as a guide to identify, calculate and distribute production costs. The methods and techniques used in this research were applied based on the need for information to be obtained, as well as field observation and as questionnaires for the formal interview. The analytical-synthetic method was applied since, it allowed to determine in a meticulous way the causes and effects that led to the problem related to production costs, the inductive method allowed to obtain general conclusions from the particular elements related to production costs for making beds and setting the price. The direct beneficiaries in this project are the owner of the Flintstone Cabinet of the La Maná canton, workers, the head of production and citizenship in general (42,216 inhabitants according to the 2010 INEC census), 1,200 students and 60 research teachers, and the Technical University of Cotopaxi with the generation of knowledge.